Dampak Pemberian Pupuk Hayati Cair terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) pada Pembibitan Utama yang ditanam di Tanah Ultisol - Z. R. Djafar; B. Irawan; F. Zulvica (Seminar Nasional Lahan Suboptimal, 2018)
Djafar et al, 2019. The Impact of Administering Liquid Biological Fertilizer on the Growth of the Palm Oil Seed (Elaeis quineensis Jacq.) in Main Nurseries Planted in Ultisol Land. pp. 193-197.The objective of this study was to see the impact of the use of liquid biological fertilizer on the growth of oil palm seedlings in the main nurseries planted in the Ultisol land. This study was conducted in Sukarami Vilaage, Alang-alang Lebar Subdistrict, Palembang City, from August 2011 to November 2011. The design of the study used was a randomized block design which was arranged factorially. The factors were the amount of fertilizer and the time to administer the liquid fertilizer. One factor consists of 4 subfactors of fertilizer dose (25%, 50%. 75%, and 100%); and the other one consists of 3 subfactors of fertilizer time (once in 5 days, once in 10 days, and once in 15 days). Each treatment was carried out with three replications. The variables observed in the plant growth were: plant height, number of leaves, stem diameter and total leaf area. The measurement was carried out every 3 weeks, until the seedlings were 3 months after planting. The study used polybags measuring 40 cm x 50 cm. The media of growth was in the from of top soil of Ultisol type, from former rubber plantation. Each polybag was filled with soil with a weight of 15 kg in dry air condition. Each polybag is labeled according to the treatment. The seeds used were from early 3-month- old nurseries. After the polybag was ready to be planted with the seedlings of 3 months old and it was placed in a open area in accordance with the treatment chart. Then it was treated and maintained. The results of the study showed that the fertilizer dosage and the time of fertilizer application and their interaction did not have an impact on the growth of the main seddlings.